Effects of insecticides commonly used in vegetable fields on survival and ovarian development of parasitoid, Pteromalus puparum - LÜ Hui-ping; YE Gong-yin; HU Cui; YAO Peng-cheng (浙江大学学报. 农业与生命科学版)
Influences of 10 insecticides at commercially recommended dosage on survival of Pteromalus puparum female adults, as well as 4 of them on the ovarian development of surviving adults, were evaluated in laboratory using dry film bioassay. Based upon the mortality of treated adults, phoxim and chlorpyrifos were considered as the most toxic insecticides for female adults of the parasitoid, followed by deltamethrin, chlorfenapyr and bisultap, and fenvalerate as the insecticide of far less toxicity than the formers; abamectin, abamectin-BT, methomyl and chlorfluazuron were fairly safe to this parasitoid. Ovarian development of surviving adults was repressed considerably by methomyl, but evidently less by abamectin, abamectin-BT and chlorfluazuron. In terms of enhancing control efficacy of P. puparum, abamectin, abamectin-BT and chlorfluazuron are recommended as insecticides of first priority for chemical control of Pieris rapae.